2013
DOI: 10.1134/s1990747813020074
|View full text |Cite
|
Sign up to set email alerts
|

The competition transport of sodium ions and protons in the cytoplasmic access channel of the Na+,K+-ATPase

Abstract: The changes in capacitance and conductance of lipid bilayer membranes have been studied with adsorbed membrane fragments containing Na + ,K + ATPase. These changes have been initiated by fast release of protons from a bound form ("caged H + ") induced by an UV flash. The changes of the capacitance in the presence of Na + ,K + ATPase were affected by the frequency of the applied voltage, pH and the concentration of sodium ions. Addition of sodium ions altered the changes of capacitance caused by a pH jump in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Measurements of the capacitance increments at alternating voltage fre quencies between 2 and 200 Hz showed that the capacitance changes did not depend on the frequency (data not shown). This fact allows us to suppose that the exchange of ions between the solution and the binding sites at the cytoplasmic side of the Na + ,K + ATРase is sufficiently fast (in contrast to the transport of sodium ions at the extracellular side, studied earlier [19]). Taking this finding into account, we further per formed measurements at 64 Hz and assumed that at this frequency the ion distribution between solution and the binding sites is in equilibrium.…”
Section: Studies Of the Competitive Binding Of Sodium Ions And Protonsmentioning
confidence: 99%
See 4 more Smart Citations
“…Measurements of the capacitance increments at alternating voltage fre quencies between 2 and 200 Hz showed that the capacitance changes did not depend on the frequency (data not shown). This fact allows us to suppose that the exchange of ions between the solution and the binding sites at the cytoplasmic side of the Na + ,K + ATРase is sufficiently fast (in contrast to the transport of sodium ions at the extracellular side, studied earlier [19]). Taking this finding into account, we further per formed measurements at 64 Hz and assumed that at this frequency the ion distribution between solution and the binding sites is in equilibrium.…”
Section: Studies Of the Competitive Binding Of Sodium Ions And Protonsmentioning
confidence: 99%
“…The results were analyzed quantitatively with the help of the model described in [19]. This model is a generalization of the model of electrogenic transport of ions in the cytoplasmic access channel of the Na + ,K + ATPase developed earlier [13].…”
Section: Studies Of the Competitive Binding Of Sodium Ions And Protonsmentioning
confidence: 99%
See 3 more Smart Citations